Blue dye for identification of sentinel nodes in breast cancer and malignant melanoma: a systematic review and meta-analysis. (February 2017) - Peek, Mirjam CL; Charalampoudis, Petros; Anninga, Bauke; Baker, Rose; Douek, Michael
The combined technique (radioisotope and blue dye) is the gold standard for sentinel lymph node biopsy (SLNB) and there is wide variation in techniques and blue dyes used. We performed a systematic review and meta-analysis to assess the need for radioisotope and the optimal blue dye for SLNB. A total of 21 studies were included. The SLNB identification rates are high with all the commonly used blue dyes. Furthermore, methylene blue is superior to iso-sulfan blue and Patent Blue V with respect to false-negative rates. The combined technique remains the most accurate and effective technique for SLNB. In order to standardize the SLNB technique, comparative trials to determine the most effective blue dye and national guidelines are required.